STRATEGI PEMBELAJARAN INOVATIF DALAM MENGHADAPI PERKEMBANGAN PENDIDIKAN: STRATEGI PEMBELAJARAN INOVATIF DALAM MENGHADAPI PERKEMBANGAN PENDIDIKAN - Rasna, Jelita Siringoringo; Rasnawati Lubis (STKIP Subang, 2026)
The rapid development of education in the modern era requires continuous innovation in the learning process to ensure its relevance to current needs. This study aims to examine innovative learning strategies as an effective approach to addressing the dynamic changes in the field of education. The method used in this research is a literature review, drawing from various academic sources such as books, journals, and scholarly articles.The findings indicate that the implementation of innovative learning strategies, such as project-based learning, problem-based learning, collaborative learning, and the integration of digital technology, plays an important role in improving the quality of the learning process. These strategies not only enhance students’ academic achievement but also foster motivation, creativity, active participation, and critical thinking skills..